Usability Assessment of the Rehabilitation Lower-limb Orthopedic Assistive Device by Service Members and Veterans With Lower Limb Loss. Issue 3 (26th February 2021) - Symsack, Allison; Gaunaurd, Ignacio; Thaper, Akshay; Springer, Barbara; Bennett, Christopher; Clemens, Sheila; Lucarevic, Jennifer; Kristal, Anat; Sumner, Matthew; Isaacson, Brad; Pasquina, Paul; Gailey, Robert
ABSTRACT: Introduction: Telehealth is an increasingly common approach to improve healthcare delivery, especially within the Veterans Health Administration and Department of Defense (DoD). Telehealth has diminished many challenges to direct access for clinical follow-up; however, the use of mobile telehealth for specialty rehabilitative care is emerging and is referred to as telerehabilitation. As early adopters of telehealth, the Veterans Affairs and DoD have supported collaborated efforts for programs designed to increase the access and quality of rehabilitative care while improving the functional ability of our service members (SMs) and veterans with lower limb amputation (LLA). The DoD and Veterans Health Administration collaborated on a Mobile Device Outcomes-based Rehabilitation Program (MDORP) to help injured SMs and veterans with LLA. The MDORP project utilized a mobile health system called the Rehabilitative Lower Limb Orthopedic Accommodating Device (ReLOAD) to assess walking quality. The ReLOAD system includes real-time auditory biofeedback to notify the user of their most prominent gait deviation and then recommends exercises that address specific balance and strength impairments. The purpose of this study was to describe the responses to a postintervention survey evaluating the feasibility and usability of ReLOAD completed by SMs and veterans with LLA who used the system for 5 months. Materials and Methods: A link to an anonymous usability survey was emailed to all participants who completed MDORP. The survey was modeled after the System Usability Scale, with agreeableness to items rated on a 5-point Likert-style questionnaire in addition to open feedback. Data visualization of Likert-style questionnaires was conducted using ggplot2 and reshape2 statistical packages and was analyzed using R. We obtained institutional review board approval through both Miami Veterans Affairs Healthcare System and Walter Reed National Military Medical Center. Results: The majority of participants reported that they would use the system again for home rehabilitation (65%) and that auditory biofeedback helped them walk better (59%). Participants also suggested that future work should include a greater variety of exercise options and the use of smart phones for the ReLOAD application in addition to the iPad tablet. Conclusions: The participants provided positive and constructive feedback that will enhance the value and usability of telerehabilitation interventions like the ReLOAD system for future users.